Structural vibration measurement with multiple synchronous cameras. (August 2021) - Del Sal, Roberto; Dal Bo, Loris; Turco, Emanuele; Fusiello, Andrea; Zanarini, Alessandro; Rinaldo, Roberto; Gardonio, Paolo
Highlights: Beam flexural vibration measurement with multi-cameras, i.e. more than 2. Multi-view, i.e. more than 2, triangulation. Influence of radial distance, opening angle and resolution of cameras. Accuracy evaluation with an increasingly larger number of cameras. Experimental measurement of beam flexural vibration with multi-cameras. Abstract: This paper presents a simulation and experimental study on the measurement with multiple, i.e. more than 2, synchronous cameras of the flexural deflection shape of a beam excited by a transverse force at the fundamental resonance frequency, which gives a good estimate of the first flexural natural mode shape. The first part of the paper presents the simplified optical model employed to simulate how the accuracy of the measurements varies with respect to: a) the distance of the cameras from the structure; b) the opening angle between pairs of cameras, which is analysed with respect to the azimuthal and elevation spherical coordinates, c) the resolution of cameras and d) the number of cameras. The second part of the paper provides experimental results taken on a beam rig and camera setup assembled using off-the-shelf devices. The study shows that the accuracy of the measurements significantly rises as the setup is equipped with an increasingly larger number of cameras, which should be arranged close to the vibrating structure with large opening angles between pairs of cameras characterized by large azimuthal and small elevation spherical coordinates. For instance, the average error of the measured flexural deflection shape falls from 15% to 3% when a setup with cameras arranged along a circumference oriented parallel the beam surface, with a small offset from the beam, passes from 2 cameras to 12 cameras.